1990
DOI: 10.1007/bf00010747
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen fixation and growth of soybean as influenced by varying the methods of inoculation with Bradyrhizobium japonicum

Abstract: The effects of inoculating soil with a water suspension of Bradyrhizobium japonicum (i) at seeding, (ii) 7, or (iii) 14 days after planting (DAP), (iv) seed slurry inoculation and (v) seed slurry supplemented with postemergence inoculation of a water suspension of Bradyrhizobium at 7 or (vi) 14 DAP, on nodulation, N 2 fixation and yield of soybean (Glycine max. [L.] Merrill) were compared in the greenhouse. The ~SN isotope dilution technique was used to quantify N 2 fixed at flowering, early pod filling and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…However, until now these techniques were used without including several factors that can optimise inoculation. Experiments that were carried out with the help of many leguminous species did not take into account the effect of the method of inoculation, the size of the inoculum, the period of inoculation or the effects of the physiological stage of the bacterial strains on nodulation and biomass production [5]. Some of the key studies carried out on the inoculation of Acacia mangium and Leucaena leucocephala are summarised in Table I.…”
Section: Introductionmentioning
confidence: 99%
“…However, until now these techniques were used without including several factors that can optimise inoculation. Experiments that were carried out with the help of many leguminous species did not take into account the effect of the method of inoculation, the size of the inoculum, the period of inoculation or the effects of the physiological stage of the bacterial strains on nodulation and biomass production [5]. Some of the key studies carried out on the inoculation of Acacia mangium and Leucaena leucocephala are summarised in Table I.…”
Section: Introductionmentioning
confidence: 99%
“…However, even though promising, the information on the effects of the utilization of liquid carriers for the inoculant is less available, as pointed out by HAMMOUD (1981) and DANSO et al (1990), among others.…”
Section: Soybeanmentioning
confidence: 99%
“…The data were derived from the study reported in detail in another paper (Danso et al, 1990), which examined the effects of various inoculation procedures on the growth and N 2 fixation in soybean (Glycine max. (L.) Merrill).…”
Section: (2)mentioning
confidence: 99%
“…For easy reference, LSD comparisons were all presented in the Tables at the 0.05 level, but where the significance was at the 0.01 level, this is stated in the text. Since treatment effects have already been reported (Danso et al, 1990), statistical comparisons between inoculation treatments have been excluded from this paper.…”
Section: (2)mentioning
confidence: 99%
See 1 more Smart Citation